Matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) in the tumors of central nervous system (CNS) - Lukaszewicz-Zajac, Marta; Mroczko, Barbara; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Neural Transmission, 2014)
Malignant neoplasms of the central nervous system (CNS) account for about 1.3 % of all tumors and 2.2 % of all cancer-related deaths. CNS tumors consist of heterogeneous group of neoplasms, including different variants of primary brain tumors and metastatic neoplasms. Advanced imaging techniques improved the neuroradiological diagnostic accuracy, although these methods are not specific enough for differentiation of CNS tumors, thus new approaches of patients' diagnosis are critically needed. The best solution for the diagnosis of patients with CNS tumors could be easily available biomarkers, which could be useful for the management of CNS neoplasms. Biomarkers should facilitate the diagnosis, monitor of treatment response and assess the prognosis of patients' survival. Currently, except for rare germ cell tumors, there is a lack of knowledge on biochemical markers for CNS neoplasms. Therefore, in this paper we summarized and referred a number of comprehensive reviews concerning the role of matrix metalloproteinases (MMPs) and their tissue inhibitors in tumor progression, including CNS neoplasms as well as described the general biochemistry of MMPs and their tissue inhibitors. Moreover, we presented the wide variety of previous findings, where authors suggested the significance of selected MMPs and their tissue inhibitors as potential biomarkers of human tumors, including CNS tumors. However, future investigations are needed to be performed before some of these enzymes could finally be used as biomarkers of specific types of CNS neoplasms.
EVALuna2:23624